Business report guides : research reports and business plans - Clippinger, Dorinda A. (Corporate communication collection., 2019)
Offers strategies for creating two complex reports. Also, it includes a complete replica of a business research report and a business plan. The guides for both reports emphasize thorough planning and preparation and take readers through these essential steps. Additional guides aid readers in writing, producing, and presenting research reports and business plans. This book is for you if you are an MBA candidate or an upper-level student in any professional field OR if you are a business manager or other professional whose career involves (1) conducting business research and generating reports for others in and outside your organization or (2) attracting investors for starting an organization or changing an existing one.